PHENOLOGY OF Copernicia alba IN FLOODED AND NOT FLOODED ENVIRONMENTS - Araujo, Maicon Marinho Vieira; Lobo, Francisco Almeida (Floresta, 2020)
The objective of this study is to describe the reproductive and vegetative phenological patterns of individuals of Copernicia alba, popularly known as "carandá", present in a flooded and non-flooded environment and to test the relations between vegetative and reproductive phenophasesand climatic seasonality. The phenological aspects of the carandá were obtained through a biweekly observation of 22 individuals from two areas of the Pantanal of Mato Grosso between August 2015 and August 2017. The carandá population presented a perennial behavior, flowering during the dry season and a greater leaf intensity in the transition period to the rainy season. Budding, although continuous, was intense in the rainy season, and the leaf deciduous pattern had a direct interference from the absence of rainfalls in the dry period. The incidence of floral buds occurred in the dry period, and the flowering occurred between the dry and rainy periods. The fruiting period occurred in the rainy season, indicating a high synchronism of phenophases.